Exploring Veteran Success Through State‐Level Administrative Data Sets. Issue 171 (May 2017) - Massa, Tod; Gogia, Laura
Abstract : This chapter describes the benefits and challenges of state‐level longitudinal data collection on student veterans and offers recommendations for optimizing collection and reporting for the advocacy of student veteran success.